DEVELOPING AN ANDROID PROTOTYPE APPLICATION TO PREDICT ROCK FRAGMENTATION FROM BLASTING IN SURFACE MINING - Hendra Harisman; Nurul Aflah; Pocut Nurul Alam; M Muchlis; Febi Mutia (Jurnal Sains dan Teknologi Reaksi, 2026)
Blasting plays an important role in surface mining operations because it directly affects rock fragmentation, which is a key factor in optimizing mining performance. However, fragmentation prediction is commonly conducted using complex mathematical calculations on computers or laptops, making the process less practical and time-consuming. This study aims to develop an Android-based application to facilitate the prediction of blasting fragmentation results in a more efficient and accessible manner. The research employed a research and development (RD) methodology consisting of application design, development, and testing stages. The results show that the developed Android application can assist mining professionals in predicting rock fragmentation practically through smartphone devices. The application improves the efficiency and accessibility of fragmentation prediction and demonstrates the implementation of digital technology in mining practices within the Industry 4.0 era. Key words: blasting, surface mining, fragmentation prediction, mining optimization, digital technology.